A framework for integrating supply chain, environmental, and social justice factors during early stationary battery research - Putsche, Victoria L.; Pattany, Jasmine; Ghosh, Tapajyoti; Atnoorkar, Swaroop; Zuboy, Jarett; Carpenter, Alberta; Takeuchi, Esther S.; Marschilok, Amy C.; Takeuchi, Kenneth J.; Burrell, Anthony; Mann, Margaret K. (Frontiers in Sustainability, 2023)
The transition to a decarbonized economy will drive dramatically higher demand for energy storage, along with technological diversification. To avoid mistakes of the past, the supply chain implications and environmental and social justice (ESJ) impacts of new battery technologies should be considered early during technological development. We propose herein a systematic framework for analyzing these impacts for new stationary battery technologies and illustrate the framework with a case study. The goal is to promote future development of technologies with secure supply chains and favorable ESJ profiles to avoid expensive corrective actions after substantial resources have been invested. This framework should be a useful tool for public and private researchers and sponsors who want to ensure that supply chain and ESJ concerns are considered and integrated as part of decision making throughout the research and development process.